Urine ‘picket fence’ crystals in ethylene glycol poisoning - Chothia, Mogamat-Yazied; Bapoo, Nabeel (African Journal of Nephrology, 2021)
A 46-year-old woman intentionally ingested ethylene glycol and overdosed on paracetamol. She had clinical and laboratory features suggestive of ethylene glycol poisoning, and examination of the urine revealed calcium oxalate monohydrate, or ‘picket fence’, crystals. She responded well to therapy that included haemodialysis. Clinicians should be aware that these crystals appear late during the evolution of ethylene glycol poisoning and, along with other clinical and laboratory findings, should prompt the initiation of haemodialysis.